2011
DOI: 10.1038/hr.2011.139
|View full text |Cite
|
Sign up to set email alerts
|

The antifibrotic agent pirfenidone inhibits angiotensin II-induced cardiac hypertrophy in mice

Abstract: Pirfenidone (5-methyl-1-phenyl-2-[ 1 H]-pyridone) is an effective drug for idiopathic interstitial pneumonia that can prevent and reverse tissue fibrosis in several organs. Therefore, we investigated whether pirfenidone has a potential role in preventing angiotensin II (Ang II)-induced cardiac hypertrophy. A cardiac hypertrophic mouse model was created using an Ang II infusion (200 ng kg À1 min À1 ) in wild-type mice for 2 weeks. Mice were divided into the following three groups: a saline-infused (control) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…This correlated with reduced protein levels of ROS, TGF-β 1 , and IL-1β in the heart. Our results confirm those of a previous study that used pirfenidone to prevent left ventricular hypertrophy and perivascular and interstitial tissue fibrosis in a mouse model of angiotensin II-induced cardiac hypertrophy [8]. In that study, the inhibition of tissue fibrosis was suggested to be due to a reduction in mRNA expression of a number of profibrotic mediators including atrial natriuretic peptide, brain natriuretic peptide, and TGF-β 1 [8].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This correlated with reduced protein levels of ROS, TGF-β 1 , and IL-1β in the heart. Our results confirm those of a previous study that used pirfenidone to prevent left ventricular hypertrophy and perivascular and interstitial tissue fibrosis in a mouse model of angiotensin II-induced cardiac hypertrophy [8]. In that study, the inhibition of tissue fibrosis was suggested to be due to a reduction in mRNA expression of a number of profibrotic mediators including atrial natriuretic peptide, brain natriuretic peptide, and TGF-β 1 [8].…”
Section: Discussionsupporting
confidence: 81%
“…Although this is a useful property for clinical use, it was noted that it induces the formation of aneuploidy in proliferating fibroblast cells, thus restricting its use for the clinical treatment of fibrosis disorders in humans. Previous studies in mouse models have suggested that pirfenidone might have universal therapeutic antifibrosis effects in different kinds of organ fibrotic diseases [6,7,8] and, therefore, pirfenidone remains one of the best choices for the development of antifibrotic drugs with which to treat cardiac fibrosis. The aim of this study was to determine whether treatment with pirfenidone, a small-molecular drug with antifibrotic properties, could ameliorate fibrosis in a mouse model of TAC-induced left ventricular hypertrophy and myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce cardiac hypertrophy, AT-II (1000 ng kg À1 min À1 ) was continuously infused subcutaneously for 14 days via an osmotic mini-pump (ALZET, Cupertino, CA, USA) 19,20 . The control group received a saline infusion.…”
Section: In Vivo At-ii Infusion and Bapn Treatmentmentioning
confidence: 99%
“…The area of interstitial fibrosis in the marginal area of the infarct was measured as described previously (14,17). Briefly, 4-mm-thick sections were cut and stained with Sirius red stain for the measurement of the area of interstitial fibrosis.…”
Section: Estimation Of Cardiac Fibrosismentioning
confidence: 99%